Modern aspects of power system frequency stability and control - Dixon, Andrew (Electrical engineer) (Academic Press, 2019)
Modern Aspects of Power System Frequency Stability and Control describes recently-developed tools, analyses, developments and new approaches in power system frequency, stability and control, filling a gap that, until the last few years, has been unavailable to power system engineers.